The Relationship Between Emotional Intelligence (EI) And The Malaysian University English Test (MUET) Performance Among Technical Students - Hamdzah, Nor Lailatul Azilah; M. Subramaniam, Indra Devi; Zainal Abidin, Nadiah; Hassan, Ruslan (IJLTER.ORG, 2020)
Past research has proven that emotional intelligence, the ability to justify one’s emotion is integral in higher education, especially in teaching and learning of English Language. The main objectives of this study are to examine i) the relationship between emotional intelligence (EI) and MUET performance among undergraduate students in the technical university, ii) the correlation between emotional intelligence and MUET performance among 250 respondents from engineering and information and communication technology (ICT) courses and iii) can the level of emotional intelligence (EI) among undergraduate students in a technical university predict the students’ performance in MUET? The cross-sectional survey design was used to collect the data from 250 respondents. The respondents were given the EQI questionnaire which had been constructed to collect the respondents’ EI, which covers these aspects; self-awareness, self-regulation, empathy, self-motivation and social skills subskills. The results have highlighted that EI has a significant correlation with the students’ MUET performance and can predict the students’ MUET performance. Also, besides that, the findings show that there is a significant difference between the students’ course and their EI level, thus implicating its dominant on education. Thus, from this study, as emotional intelligence plays important roles in determining the students’ English language performance, emotional intelligence skills should be embedded in designing the English course. For future research, it is also recommended to discover the relationship of emotional intelligence traits and other language skills such as listening, speaking, reading and writing.